CLOUD POINT PRECONCENTRATION OF AMLODIPINE FROM BIOLOGICAL LIQUIDS FOR HPLC MS/MS DETERMINATION: UDC 543.3, 542.61, 611.185.1 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
A high performance liquid chromatography method with cloud point preconcentration was developed for determination of amlodipine in synthetic urine. Non-ionic surfactant Triton X-100 as an environmentally friendly solvent was used for the micelle-mediated extraction.  The influence of some parameters such as the concentration of Triton X-100, effect of the pH, incubation time, equilibration temperature and centrifugation on effectiveness of cloud point extraction was studied. The complete extraction of amlodipine into the surfactant-rich phase was achieved by using 2.0 % (w/v) solutions of Triton X-100, the pH > 8.0. Amlodipine, under such conditions, exists in a hydrophobic electroneutral molecular form, that promotes its efficient extraction into the surfactant-rich phase. During the study, it was found that full extraction (R ≈ 99 %) of amlodipine in the surfactant-rich phase of Triton X-100 was achieved when initial surfactant concentration was  above 0.5% (CNS > 0.5 % (w/v)). The suggested method for the HPLC-MS/MS determination of amlodipine in synthetic urine with preliminary cloud point extraction was validated. The calibration curve was linear in the range on 0.08-50.00 ng mL–1. The limits of detection (3σ) and quantification (10σ) were 0.02 ng mL–1 and 0.08 ng mL–1 respectively. The matrix effect (96 %), recovery of the extraction procedure (95 %) and overall “process efficiency” (91 %) were also estimated. All validation data is consistent with international acceptance criteria and observed matrix effect is not significant. The suggested method with cloud point preconcentration exceeds the analogous methods, based on extraction using organic solvents, in the sensitivity, metrological characteristics, ecological safety and simplicity.
Keywords: cloud point extraction; non-ionic surfactants; amlodipine; mass-spectrometry